A EFEKTIFITAS PENGGUNAAN METODE TUTOR SEBAYA BERBANTUAN GAME EDUKASI BAAMBOOZLE TERHADAP HASIL BELAJAR MATEMATIKA SISWA - katili, sukri (JURUSAN PENDIDIKAN GURU SEKOLAH DASAR, 2024)
This research aimed to determine the effect of peer tutoring methods assisted by educational games on the mathematics learning outcomes of students in Grade III at SDN 11 Kabila. This research used a quantitative approach with a Pre- Experimental Design method of the One Group Pre-test Post-test Design type. The independent variable in this study was the peer tutoring method assisted by the Bamboozle educational game, and the dependent variable was the learning outcomes. Additionally, the hypothesis testing in this study used the t-test. Based on the conducted hypothesis test, it was found that the t eprr = 9.818 >= dhc t cot Ac of 2.100, with the criterion that if the calculated t cont is smaller H_0 is confirmed and H_1 is rejected. It can also be seen based on the significant value of 0 <= 0.05 with the criterion that if the significant value is smaller than 0.05, then H_0 is rejected and H_1 is confirmed. From the two criteria above, it can be concluded that H_0 is rejected and H_1 is confirmed, which means there is an effect of the peer tutoring method assisted by the Bamboozle educational game on the learning outcomes of students in Grade III at SDN 11 Kabila.